Cytomegalovirus antibody and vascular pathology in renal transplant recipients - Price, Patricia; Lee, Silvia; Affandi, Jacquita; Parsons, Richard; Naylor, L.; Watts, G.; Irish, A. (WILEY-LISS, 2017)
Cytomegalovirus (CMV) has been linked with vascular pathology and is a common complication of renal transplantation. We addressed whether CMV seropositivity influences vascular pathology several years after transplant. Levels of CMV antibody increased with age, were higher in transplant recipients than healthy controls (P < 0.001), and correlated with vascular endothelial function measured by flow mediated-dilation of the brachial artery (FMD). However, the optimal general linear model predicting FMD included CMV seropositivity as a marginal effect (P = 0.068), with age (P = 0.013), gender (P < 0.0001), and transplantation (P < 0.0001). Other measures of the burden of CMV are being tested as CMV prophylaxis is feasible as an approach to reduce vascular disease.